EXPLORING THE APPLICATION OF THE THREE PILLARS OF STUDENT ENGAGEMENT AND CLASSROOM CULTURE - Fancubila, Aurelio D. (IDEAS: Journal of Management & Technology, 2024)
Student engagement is a great factor that influences a good classroom culture and emboldens students to learn and thrive. Having a good classroom culture will help students learn the best of their abilities and increase their achievements. Utilizing a descriptive correlational approach, this study aimed to determine the degree of application of the three (3) pillars of student engagement and classroom culture of 332 randomly selected Junior High teachers. A validated and reliability tested questionnaire was used to gather the needed data from randomly selected respondents. Statistical tools used to analyze and interpret the data were frequency count, percentage, mean, t-test, analysis of variance, and Pearson r. The findings of the study revealed that respondents themselves perceived their application of the three pillars of student engagement and classroom culture as “very high” respectively. There was no significant difference in the degree of application of the three (3) pillars of student engagement when respondents were grouped according to their sex, age, and highest educational attainment, except in length of service. There was no significant difference existed in the level of classroom culture when Junior High School teachers were grouped according to sex, age, highest educational attainment, and length of service. Generally, the degree application of the three (3) pillars of student engagement is significantly related to the level of classroom culture. Thus, student engagement fosters positive classroom culture. It is therefore recommended that teachers should highly utilize student engagement such as cognitive, affective and creative into their teaching practices to promote positive classroom culture, an environment conducive to learning and self-development.